2005
DOI: 10.1097/01.scs.0000179753.14037.7a
|View full text |Cite
|
Sign up to set email alerts
|

Speech Aerodynamics and Nasalance in Oral Cancer Patients Treated with Microvascular Transfers

Abstract: The purpose of the current study was to assess speech aerodynamics and nasal acoustic energy during a follow-up period of 12 months in patients having undergone microvascular free flap reconstruction after tumor ablation from the oral cavity or oropharynx, usually followed by radiotherapy. Velopharyngeal function was assessed in terms of velopharyngeal orifice size by a pressure-flow measurement technique as well as by determining the instrumental correlate of perceived nasality (i.e., nasalance) during speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
0
20
0
3
Order By: Relevance
“…Among the 22 studies, 10 include more than 20 patients, and also 10 include between 2 and 18 subjects . Two articles do not report the number of subjects involved in the acoustic analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 22 studies, 10 include more than 20 patients, and also 10 include between 2 and 18 subjects . Two articles do not report the number of subjects involved in the acoustic analysis .…”
Section: Resultsmentioning
confidence: 99%
“…6 (18) 96.1 (16) ¼ to ½ full thickness defect X(n) 15.1 (18) 20.0 (17) 15.9 (16) 14.3 (13) 0.3 (17) 4.7 (16) 3.1 (16) 2.5 (11) 98.1 (18) 92.1 (15) 88. 6 (17) 92.4 (12) Normal mean range 17,21,24 11.9-13.7% (Average SD acoustic and aeromechanical results appear to be dependent on the extent of resection and the type of surgical reconstruction performed. For individuals with smaller resections (ie, less than half of the soft palate) and therefore less extensive reconstructions, the acoustic and aeromechanical results were within normal limits.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Although these studies provide useful information on intelligibility of speech, they do not report on acoustic and aeromechanical data related to the speech signal, which provide extra insight into the function of the soft palate during speech. 12 A previous study completed by Seikaly and colleagues 13 revealed that palatal reconstruction yielded close-to-pretreatment levels of intelligibility for most patients. However, acoustical and aeromechanical measures of speech were abnormal in patients with larger resections, indicating that the quality (ie, resonance) of the speech signal was abnormal.…”
mentioning
confidence: 95%
“…Speech raters often mistook /k/ for /x/ [7,12] . For /k/ the duration of air pressure release (the so-called plosive) as a percentage of the total duration (short silent period of pressure building + the pressure release) was measured and used as outcome measure.…”
Section: Acoustic-phonetic Analysesmentioning
confidence: 99%
“…This difference is due to the oropharyngeal area that is involved in the partition between the oral and nasal cavity. In case of failing velar closure, air escapes through the nose, which results in hypernasal characteristics of speech [12] . Objective measurements of speech quality are less often performed.…”
Section: Introductionmentioning
confidence: 99%